Enhancing Digital E-Commerce Adoption and Equity in India: The Impact of the ONDC Network on MSMEs - Ghosh, Samiran (Digital Repository of Theses, 2025)
This mixed-methods study examines the Open Network for Digital Commerce (ONDC) initiative's impact on 127 Indian MSMEs, contributing to digital commerce theory and practice. The research addresses how protocol-based interoperability affects market concentration, digital equity, and MSME competitiveness. Key findings reveal that digital literacy emerges as the primary adoption barrier (56.7%), with significant urban-rural disparities. ONDC demonstrates substantial economic benefits, including 71.7% commission rate reductions and decreased market concentration (HHI: 2567 to 1986). However, persistent challenges include data advantages (32.3%), privacy implementation gaps (22.1-29.2pp), and trust-building in distributed networks (41.7% cite platform familiarity advantage). The study makes three theoretical contributions: (1) reconceptualizing digital divide theory as multi-dimensional rather than binary; (2) providing empirical validation of protocol-based competition interventions; and (3) advancing distributed trust architecture theory. Four distinct MSME segments emerged—Digital Enthusiasts (32%), Digital Converts (41%), Digital Hesitants (18%), and Pragmatic Evaluators (9%)—each requiring differentiated support strategies. Practical implications include evidence-based frameworks for addressing adoption barriers, building digital capabilities, and strengthening competitive impact. The research demonstrates that while ONDC creates meaningful structural benefits, complementary interventions addressing capability development and trust mechanisms are essential for inclusive digital transformation. This study provides critical insights for policymakers, ONDC governance, and MSMEs navigating digital commerce transformation, while contributing to theoretical understanding of open network ecosystems in emerging economies. Keywords: ONDC, MSMEs, digital commerce, platform competition, digital divide, India.